PURE PALM OIL SPRAY CHARACTERISTICS OF DIESEL FUEL INJECTOR - Mamola, Randi; Nurcholik, Samsu Dlukha; Prahmana, Rico Aditia; Juangsa, Firman Bagja; Pratama, Raditya Hendra; Prihasto, Bima; Suardi, Suardi; Sa’adiyah, Devy Setiorini (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
Diesel engines are widely used in many sectors due to their advantages of high energy density. To reduce emissions in diesel engines, a step that can be taken is to use renewable biofuel such as pure palm oil, which has a high viscosity and is difficult to get a fine atomization process in fuel spraying. However, a detailed analysis of the spray characteristics using pure palm oil fuel on conventional diesel engines has yet to be available. In this research, high-speed imaging was conducted to investigate the spray characteristics of pure palm oil compared to diesel fuel. The result shows that (1) at the start of the injection stage, both pure palm oil and diesel fuel have similar shapes, (2) the spray angle of pure palm oil is smaller due to orifice wall cavitation not occurring in the orifice, (3) and at the end of the injection stage, pure palm oil has larger droplets, which is also more difficult to atomize.